2015
DOI: 10.1186/s12882-015-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Urate lowering therapy to improve renal outcomes in patients with chronic kidney disease: systematic review and meta-analysis

Abstract: BackgroundHyperuricemia may contribute to renal injury. We do not know whether use of treatments that lower urate reduce the progression of chronic kidney disease (CKD) and cardiovascular disease. We performed a systematic review and meta-analysis of randomized controlled trials to assess the benefits and risks of treatments that lower urate in patients with stages 3-5 CKD.MethodsWe searched MEDLINE, EMBASE, CENTRAL, Web of Science and trial registers for randomized controlled trials (RCTs) without language re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 58 publications
4
97
1
5
Order By: Relevance
“…Hyperuricaemia, a prerequisite for gout, is related to the metabolic syndrome and is an independent danger factor for chronic kidney illness, stroke and perhaps ischaemic heart disease .It is connected with multiple damaging health results, including hypertension, heart disease and is involved as 3910 an important facet of the metabolic syndrome [6] . Furthermore, hyperuricaemia is currently being considered as a modifiable danger element for deterioration of renal function [7] . The management of gout is complexed by the episodic nature of the disease.…”
Section: Allopurinol Decisions In Primary Carementioning
confidence: 99%
“…Hyperuricaemia, a prerequisite for gout, is related to the metabolic syndrome and is an independent danger factor for chronic kidney illness, stroke and perhaps ischaemic heart disease .It is connected with multiple damaging health results, including hypertension, heart disease and is involved as 3910 an important facet of the metabolic syndrome [6] . Furthermore, hyperuricaemia is currently being considered as a modifiable danger element for deterioration of renal function [7] . The management of gout is complexed by the episodic nature of the disease.…”
Section: Allopurinol Decisions In Primary Carementioning
confidence: 99%
“…Statistically significant reductions in serum uric acid, systolic, and diastolic blood pressure were found, favoring allopurinol, but there were insufficient data for analysis on adverse events, incidence of end stage renal disease (ESRD), and CV disease. The authors concluded that data are promising, but adequately powered randomized clinical trials are needed to establish whether treatments that lower urate have beneficial renal effects 10 . Observational studies were unable to capture the link between uric acid and CKD, because of methodological inadequacy.…”
Section: Drawbacks Of Published Evidencementioning
confidence: 99%
“…Definitive evidence of a causal relationship of hyperuricemia with CKD has not been produced, and large-scale clinical trials testing the effect of urate lowering therapy on major clinical end-points of CKD progression are still lacking 9 . Recently, the efficacy and the risks of urate lowering therapy to improve outcomes in patients with CKD were evaluated by a systematic review of currently published studies, and a meta-analysis of results was carried out 10 .…”
Section: Drawbacks Of Published Evidencementioning
confidence: 99%
“…Treatment of CKD patients with estimated GFR of 40.6 ± 11.3 mL/min with allopurinol 100 mg/d was associated with significant decrease in renal events (need of dialysis, doubling of serum creatinine or > 50% reduction of GFR) and cardiovascular events in comparison to control CKD patients taking only their standard treatment (P < 0.004 and 0.02 respectively) [102] . In addition, a recent meta-analysis showed a significant favorable effect of allopurinol on the rate of GFR decline [103] . Another recent trial demonstrated the significant impact of febuxostat on CKD progression in stage G3 and G4 patients [104] .…”
Section: Pathogenesismentioning
confidence: 99%